(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research note has two objectives. One is to concisely explain a theoretical discourse which the Japanese philosopher Hitoshi Imamura propounds in the first part of his article titled “Studying Economy: Make the Drive for Meaning our Primum Mobile”. The other is, by expanding Imamura’s ideas, to derive insights beneficial to the contemporary era. To achieve them, the discussion employs explicative reading as its method and develops as follows. After an introduction mentioning a previous study on Imamura’s thought, the first section dissects Imamura’s line of reasoning and demonstrates that Imamura essentially advances the following thesis: A human is a being that is unable to be content with the world as it is and inevitably and constantly looks for a (concealed) meaning. The second section explicates Imamura’s observations which relate to the proposition and whose potentialities Imamura does not fully exploit. Thereupon, it concludes that, by acknowledging that each individual lives in a unique network of meanings but that the meanings are correctable, we can amend the present world some have qualified as “post-truth”